Pemilihan Moda Transportasi Udara Terhadap Frekuensi Penggunaan Transportasi Udara Bandara Matahora - Sufrianto, Sufrianto; Sudardjat, Catrin; Aris Munandar, Fikri; Akbar, Ade (Universitas Sulawesi Tenggara, 2024)
This research aimed to determine the characteristics of users of transportation modes and to find out the frequency of using air transportation at Matahora Airport. The research method used was quantitative with a descriptive approach, which involved depicting and explaining in detail the issues studied based on the data collected in the field. The data collection technique in this research used a questionnaire, where respondents were asked to answer a number of questions about the characteristics and factors influencing the choice of air transportation. Data analysis was conducted using descriptive data analysis to explain the data obtained through a questionnaire. The research results indicated that the characteristics of mode selection for transportation were based on reasons influencing the selection of modes from a total of 60 respondents. The analysis of the characteristics of air passenger travelers showed the largest percentage in the male gender at 68%, age between 36-45 years at 41%, the highest education level being a bachelor's degree at 62%, self-employed occupation at 36%, the reason for using air transportation being faster travel time at 93%, and the influence of mode selection on the frequency of air transportation use simultaneously at 33.4%. Partially, the factors influencing the choice of air transportation mode on frequency were cost at 26.1%, security at 12.1%, and comfort at 9.1%.